2022
DOI: 10.1088/1755-1315/981/2/022040
|View full text |Cite
|
Sign up to set email alerts
|

Formation of stable agrocenoses of corn hybrids in a sharply continental climate

Abstract: The article considers the factors influencing the stability of agrocenoses of corn hybrids in the forest-steppe zone of the Krasnoyarsk Territory. The researches were carried out for three years in the zone of sharply continental climate of the Krasnoyarsk forest-steppe on leached low- and medium-thick chernozems. The main factors influencing the stability of agrocenoses of corn hybrids were determined. So the factor of climatic conditions affects the corn hybrids, its influence is no more than 14%. The factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…According to Litvinova et al [28], correlation analysis revealed a significant effect of maize height on green biomass yield. It was found that as maize height increases, the cob biomass decreases, which significantly decreases the total green biomass.…”
Section: Figurementioning
confidence: 99%
“…According to Litvinova et al [28], correlation analysis revealed a significant effect of maize height on green biomass yield. It was found that as maize height increases, the cob biomass decreases, which significantly decreases the total green biomass.…”
Section: Figurementioning
confidence: 99%
“…The average crop height was highly affected by the cultivation of single crops, as the scores for single crops of maize and hemp were well above the assessment threshold, whereas the score for the single faba bean crop was significantly lower (Figure 2). A correlation analysis by Litvinova et al [26] revealed a significant effect of maize height on green biomass yield. They found that as maize height increased, the cob biomass decreased, which significantly decreased the total green biomass.…”
Section: Level 1: Total Dried Crop Biomassmentioning
confidence: 99%
“…The assessment scores for these crops were above the threshold. The CO2 score A correlation analysis by Litvinova et al [26] revealed a significant effect of maize height on green biomass yield. They found that as maize height increased, the cob biomass decreased, which significantly decreased the total green biomass.…”
Section: Level 2: Co2 Emission From the Soilmentioning
confidence: 99%